Attributional style and academic achievement in a sample of black primary school children - Mayer, Aliza (My University, 2014)
This study examined the role that attributional style played in the academic achievement and school performance of a sample of 150 black primary school learners in grades 5 and 6 in an inner city school in the Johannesburg area. The Children’s Attributional Style Questionnaire (CASQ, 1984) was administered to determine the attributional styles. The questionnaire was comprised of 10 subscales and from this an overall level of optimism or pessimism was obtained. The academic achievement of the learners was measured by obtaining the end of year academic results of 1997 and 1998 from the mark schedules of each teacher. The results did not reveal significant correlations between attributional styles and academic achievement. This was contradictory to the existing literature. It appears that, in this disadvantaged group in South Africa, it is not attributional style that impacts upon academic achievement and school performance. However it appears that learned helplessness in terms of Seligman and Maier’s (1967) original formulation, rather than attributional style as in the reformulated theory of Abramson, Seligman & Teasdale (1978) may impact upon academic achievement in this community.
Keywords: Blacks--Education (Elementary)--South Africa.; School children--South Africa; Cognitive psychology